2013
DOI: 10.1097/mbp.0b013e32835d126c
|View full text |Cite
|
Sign up to set email alerts
|

Linking clinic and home

Abstract: Objective Older adults with chronic kidney disease have a high rate of uncontrolled hypertension. Home monitoring of blood pressure (BP) is an integral part of management, but requires that patients bring records to clinic visits. Telemonitoring interventions, however, have not targeted older, less technologically-skilled populations. Methods Veterans with stage 3 or greater chronic kidney disease and uncontrolled hypertension were randomized to a novel telemonitoring device pairing a Bluetooth-enabled BP cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 19 publications
0
58
0
11
Order By: Relevance
“…The authors found improvement in BP in both groups with no statistically differences. 25 Participants using the home-based tele-monitoring device transmitted significantly more readings to their providers than the usual care participants reported at clinic. The intervention was well received by both participants and clinicians, and was determined to be cost-effective.…”
Section: Promise and Limitations Of Telemedicine In Ckdmentioning
confidence: 97%
“…The authors found improvement in BP in both groups with no statistically differences. 25 Participants using the home-based tele-monitoring device transmitted significantly more readings to their providers than the usual care participants reported at clinic. The intervention was well received by both participants and clinicians, and was determined to be cost-effective.…”
Section: Promise and Limitations Of Telemedicine In Ckdmentioning
confidence: 97%
“…Although there is no reason this should not be the case in patients with hypertension and CKD, the data in this population are still limited. A small RCT of home BP telemonitoring in older patients with CKD and uncontrolled hypertension showed that this was feasible in this population [18]. A larger study showing effectiveness for BP control from telemonitoring and pharmacist BP management included almost a fifth of individuals with CKD [19].…”
Section: Diagnosis Classification and Evaluation Of Hypertensionmentioning
confidence: 99%
“…We compared our use of technology including self-monitoring, automated transmission without need for patient BP data upload, and responsive provider driven medication management with the 13 RCT listed in the AHA statement. We found that 10/13 had some element of SMBP with home BP monitors, 18–27 only 4/13 had automated BP transmission. Of these, two were using modem based upload 25,27 and two had Bluetooth technology.…”
Section: Discussionmentioning
confidence: 80%
“…Of these, two were using modem based upload 25,27 and two had Bluetooth technology. 18,23 Furthermore, 6/13 had responsive provider driven anti-hypertensive medication management 18–21,26,27 and an additional 2/13 had medication management in office visits where SMBP data was used 22,23 . The low numbers of trials with automated transmission reflects the earlier time frame of these studies with many of them reported between 2008 and 2013.…”
Section: Discussionmentioning
confidence: 99%